Augmented Visual Models of Scientific Zoological Collections. A User Experience at the MUSA University Museum (diségno, 2022)
The present work wants to configure itself as a paradigmatic contribution proposing a methodological approach for an augmented fruition of museums and their exhibits. Currently heritage, museums and the way of experiencing them are undergoing a paradigm shift, due to all the digitalization era, where it has to overcome this transition and take advantage of it, capitalizing on what these new technologies have to offer.An augmented fruition experience of a study case is proposed, where the augmented component is configured by combining state-of-the-art techniques with traditional ones. Where rapid prototyping, different survey techniques and augmented reality in fusion with the standard ways of showcasing objects are used, in the museum center of agricultural sciences (MUSA) of the University of Naples Federico II in Portici. The augmented fruition for all heritage of the museum is the outcome of a three-way relation made between the new technologies and the two key concepts: preservation and divulgation. Where the technologies offer ways to develop strategies, more efficiently, for divulgation and preservation; and the second two facilitate a field of application for pushing the limit of these technologies further and further.
Keywords: scientific collections; cultural heritage; extended realities; rapid prototyping; virtual fruition model